(untitled) (Journal of Hama University, 2022)
Women around the world are suffering from breast cancer which is consided the most common cancer affecting them. The mortality rate can be decreased with a contentious and regular screening of the breast especially by breast self-examination. Assessment of Breast Self-Examination Practice among Female Employees in Tishreen University.A descriptive quantitative cross-sectional study conducted on a cluster random sample of 114 female employees in Tishreen University from 1/11/2021 to 5/11/2021. Data collected by using questionnaire which is designed by the researchers. The majority of the participants made a mistake in all steps on the checklist that was prepared for this purpose, and they didn’t do it the right way. More than tow third of the study sample had poor practice of breast self-examination (69.3%), 19.3% determined average level of practice, only 11.4% had good level of practice. This study recommended that breast self-examination educational programs are necessary to improve practice and awareness of women about this important procedure, in addition to encouraging more research to reveal any association between demographic characteristics, health habits, level of knowledge, attitudes and practice of breast self-examination.